On the welfare role of redundant assets with heterogenous forecasts - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2023)
We study a multiperiod model with a nominal bond that matures in one period and identify the set of e¢ cient allocations that can be sustained as Walrasian equilibria with heterogeneous forecasts. We next add a long maturity bond, which under perfect foresight would be a redundant asset, and show that it fundamentally expands the set of e¢ cient allocations that can be sustained as Walrasian equilibria. Indeed all wealth transfers compatible with e¢ ciency can arise endogenously. The key feature driving this conclusion are forecasting errors, which lead to ex post arbitrage opportunities that induce these income transfers.